ANALYSIS VARIABLES AFFECTING THE HOUSEHOLD DEMAND FOR KEROSENE FUEL IN INDONESIA - Kawung, George M. V. (Fakultas Ekonomi, UIN Maliki Malang, 2008)
This research is aimed: (a) to discover the variables affecting the household demand for kerosene fuel in Indonesia, (b) to know the dominant variables found above. The research used time series data from 1995-quarter I to 2004-quarter-IV, by using Dynamic Linear Model (DLM) approach by Error Correction Model (ECM). The results showed that (a) in the short term, household demand for kerosene fuel in Indonesia is affected by kerosene price itself, per capita income, and population number. While at long term, it is affected by per capita income and population number. (b) The most dominant variables affecting the household demand for kerosene fuel in Indonesia was the kerosene fuel price.